Vibrations of a spherical shell. Comparison of 3-D elasticity and Kirchhoff shell theory results - Chang, Yao-Chang; Demkowicz, Leszek (Computer Assisted Methods in Engineering and Science, 2023)
Natural frequencies of a vibrating hollow, elastic sphere are determined using both the 3-D elasticity and Kirchhoff shell theory.